Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Tevtia, Amit K.; Singh, R. P. (Polymer Degradation and Stability, 2006)
The stabilization of polyolefins against gamma-sterilization has been studied with single or binary additive system. The present attempt is to utilize synergistic mixtures of stabilizers which are approved for food contact applications. Ethylene-propylene (EP) copolymer has been melt-mixed with hindered amine stabilizers (HAS), phenolic antioxidants and organo-phosphites (hydroperoxide decomposer). Samples were sterilized with different doses of gamma-radiation. Stabilization was characterized in terms of changes in the functional groups (oxidation products), tensile properties, yellowing and surface morphology by FTIR spectroscopy, Instron, colorimetry (reflectance) and scanning electron microscopy (SEM), respectively. Results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol system. Among phenol containing systems, where we mostly observe discoloration due to the oxidation of hindered phenol and the combination of secondary HAS, tertiary HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The mixture of secondary HAS and tertiary HAS, has shown antagonistic effect of stabilization whereas their combination with organo-phosphite has exhibited synergistic effect of stabilization even at higher doses of gamma-sterilization. The effects have been explained through the interaction between the stabilizers. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Antioxidants; discoloration; ethylene-propylene copolymer; gamma-sterilization; stabilization; tensile properties

Stabilization of gamma-sterilized biomedical polyolefins by synergistic mixtures of oligomeric stabilizers. part II. polypropylene matrix - Alariqi, Sameh A. S.; Kumar, A. Pratheep; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2007)
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction